Study on in vitro Propagation of Japanese Honeysuckle (Lonicera japonica Thunb.) via the Callus Method - Trang, Ngo Thi; Luan, Nguyen Thanh; Hang, Pham Thi Luong (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The purpose of this study was to propagate the japanese honeysuckle species ( Lonicera japonica Thunb.)  via callus formation. We described callus induction in young leaves and shoot tip explants of this species, their proliferation and shoot regeneration from the callus. Both explants were cultured on MS medium supplemented with growth plant regulators (2.4-D; NAA and BAP) for callus induction. Our results showed that callus formation from shoot tip explants was better than that  from leaf explants with white in color and soft callus when cultured on MS medium containing 1.5 mg/l of BAP. Callus formation from this medium was 92.31% successful with an average length size of 1.8 cm. After four weeks of callus induction in a completely dark condition, calli were transferred for two weeks to brightly light conditions for callus proliferation on MS medium supplemented with 0.5 mg/l of BAP in which calli increased five times in size. Calli were luxuriant and pale green in color. Shoots were regenerated from the callus on MS medium containing 1 mg/l of BAP in which 100% of cultured callus pieces produced adventitious shoots with shoot numbers ranging from 14 to 20 per callus. Keywords: Callus, in vitro propagation, Lonicera japonica , medicinal plant.